Investigating Ramifications of Climate Change on Farming Practices and Sustainable Livelihood Preferences for Farmers in Tropical Regions - Timothy O. Ogunbode; Timothy A. Akinkuolie; Victor O. Oyebamiji (International Journal of Agronomy)
The continuity of farmers in farming under the impacts of climate change (CC), especially in developing nations, is still less investigated in literature. A survey was conducted among 220 farmers in selected rural communities in Ondo, Nigeria. The data were subjected to both descriptive and inferential statistical analyses. The results showed that male gender formed 90% of the respondents, 68% of the respondents cultivate up to 15 acres of farmland while 61% had experienced a decrease in their farmland sizes between 2000 and 2023 of which 47% (103 out of 220) claimed was due to erratic rainfall. Factor analysis identified and extracted three significant options for the sustainability of farmers’ living in the CC era, namely, (i) adoption of soil and water conservation option (35.007%); (ii) abandonment of farming for another means of livelihood (15.052%) and (iii) reduction in the farmland size (11.774%). However, in view of the combined weights of options (i) and (iii) ([74.57% of the absolute value]) which explained farmers’ preference to remain in farming, it, thus, implied that farmers will rather take options that will keep them in framing despite the impact of CC rather than abandoning it. The results are indications of the prevalence of CC and the policies that will enhance farming in CC era to be put in place to sustain the livelihood of farmers. Further studies are suggested on enhancing farmers’ livelihood to keep them in agriculture in the CC era.